Increased Frequencies of Myelin Oligodendrocyte Glycoprotein/MHC Class II-Binding CD4 Cells in Patients with Multiple Sclerosis - Raddassi, Khadir; Kent, Sally C; Yang, Junbao; Bourcier, Kasia; Bradshaw, Elizabeth M; Seyfert-Margolis, Vicki; Nepom, Gerald T; Kwok, William W; Hafler, David A (The Journal of immunology (1950), 2011)
Multiple sclerosis (MS) is an autoimmune disease characterized by infiltration of pathogenic immune cells in the CNS resulting in destruction of the myelin sheath and surrounding axons. We and others have previously measured the frequency of human myelin-reactive T cells in peripheral blood. Using T cell cloning techniques, a modest increase in the frequency of myelin-reactive T cells in patients as compared with control subjects was observed. In this study, we investigated whether myelin oligodendrocyte glycoprotein (MOG)-specific T cells could be detected and their frequency was measured using DRB1*0401/MOG97–109(107E-S) tetramers in MS subjects and healthy controls expressing HLA class II DRB1*0401. We defined the optimal culture conditions for expansion of MOG-reactive T cells upon MOG peptide stimulation of PMBCs. MOG97–109-reactive CD4+ T cells, isolated with DRB1*0401/MOG97–109 tetramers, and after a short-term culture of PMBCs with MOG97–109 peptides, were detected more frequently from patients with MS as compared with healthy controls. T cell clones from single cell cloning of DRB1*0401/MOG97–109(107E-S) tetramer+ cells confirmed that these T cell clones were responsive to both the native and the substituted MOG peptide. These data indicate that autoantigen-specific T cells can be detected and enumerated from the blood of subjects using class II tetramers, and the frequency of MOG97–109-reactive T cells is greater in patients with MS as compared with healthy controls.